Association between smoking-related attentional bias and craving measured in the clinic and in the natural environment - Begh, R; Smith, M; Ferguson, S; Shiffman, S; Munafò, M; Aveyard, P (American Psychological Association, 2016)
Previous laboratory studies have investigated associations between attentional bias and craving, but ecological momentary assessment (EMA) may provide ecologically-valid data. This study examines whether clinic-measured attentional bias is associated with noticing smoking cues, attention to smoking, and craving assessed by EMA and whether EMA-assessed cues and attention to smoking are associated with craving in a secondary analysis of data from 100 cigarette smokers attempting cessation. Two weeks before quitting, participants completed attentional bias assessments on visual probe (VP) and Stroop tasks and completed random EMA-assessments for seven weeks thereafter. Participants completed 9,271 random assessments, averaging 3.3 prompts/day. Clinic-measured attentional bias was not associated with cues seen (VP: OR = 1.00, 95% CI = [0.99, 1.01]; Stroop: OR = 1.00, 95% CI [0.99, 1.00]), attention toward smoking (VP: OR = 1.00, 95% CI [0.99, 1.02]; Stroop: OR = 1.00, 95% CI [0.99, 1.00]), or craving (VP: OR = 1.00, 95% CI [0.99, 1.02]; Stroop: OR = 1.00, 95% CI [0.99, 1.01]). EMA responses to seeing a smoking cue (OR = 1.94, 95% CI [1.74, 2.16]) and attention toward smoking (OR = 3.69, 95% CI [3.42, 3.98]) were associated with craving. Internal reliability was higher for the Stroop (α = .75) than visual probe task (α = .20). In smokers attempting cessation, clinic measures of attentional bias do not predict noticing smoking cues, focus on smoking, or craving. However, associations exist between noticing smoking cues, attention toward smoking, and craving assessed in the moment, suggesting that attentional bias may not be a stable trait. (PsycINFO Database Record